Acute motor and sensory polyganglioradiculoneuritis in a cat: clinical and histopathological findings. Issue 2 (February 2015) - Gutierrez-Quintana, Rodrigo; Cuesta-Garcia, Nerea; Wessmann, Annette; Johnston, Pamela; Penderis, Jacques
Polyneuropathies can have a variety of clinical presentations and tend to be rare in cats. In this report we describe a 6-year-old domestic shorthair cat with an acute and rapidly progressive onset of lower motor neuron and sensory signs affecting the spinal and cranial nerves. Histopathological examination revealed moderate-to-severe multifocal inflammatory infiltrates at the ventral and dorsal nerve roots, and dorsal spinal ganglia at the level of the L4 and cauda equina. The type and severity of inflammation varied between nerve roots, being composed of mainly neutrophils in some and mainly lymphocytes and macrophages in others. Immunohistochemistry showed a combination of neutrophils, macrophages and lymphocytes infiltrating the nerve roots and ganglia. The majority of the lymphocytes were T lymphocytes; only a few B lymphocytes were seen. Neurons within the affected ganglia showed central chromatolysis and necrosis. Wallerian-like degeneration and demyelination were observed in the nerve roots. A sensory and motor polyganglioradiculoneuritis was diagnosed. An autoimmune process similar to the acute motor and sensory neuropathy subtype of Guillain–Barré syndrome in humans or an infection by an unidentified agent were considered most likely.